Demographic situation of the regions of the Russian Federation in the current epidemiological conditions - S. A. Bannikov; L. M. Tuktamysheva; O. I. Bantikova; O. I. Stebunova (Вестник университета, 2025)
The relevance of the study is due to the need to assess the scale of the deep and often unpredictable influence of epidemiological, economic and political factors on key demographic indicators. Assessment of the current state as well as prospects for the development of the demographic situation in the regions of the Russian Federation (hereinafter referred to as RF, Russia) will allow timely identification of problems and development of measures to mitigate them, making sound strategic decisions in the interests of a particular region of the RF. The purpose of the study is to analyse and forecast the demographic situation in the regions of Russia. To achieve this goal, the article uses data visualisation methods, cluster and regression analysis, forecasting series with a structural shift. The results of the cluster analysis, indicating the territorial heterogeneity of the constituent entities of the RF in terms of demographic status, are used in an econometric model that makes it possible to assess the impact of a number of factors on mortality. In particular, it is found that population density, the proportion of the population over working age, that is, factors that, in turn, are associated with the consequences of coronavirus infection and its negative impact on the elderly population, have a significant impact on the overall mortality rate. The death toll forecast showed that the pandemic contributed more than 53 thousand deaths per month, including not only deaths from coronavirus infection, but also deaths indirectly related to the introduction of restrictions on planned hospitalisation, a drop in the standard of living of the population, etc. Mortality decreased to the level of mortality observed before the COVID-19 pandemic by mid-2023, but already in January 2025 the number of deaths may exceed 170 thousand people per month. Further studies are planned to model and forecast indicators of the demographic state of the regions of the RF based on various scenarios for the development of the epidemiological situation as well as considering the economic and foreign policy situations.